Pelatihan Pembuatan Pupuk Organik Cair (POC) Berbahan Kulit Pepaya dan Hama Keong Mas (Kul) Sebagai Upaya Minimize Cost Pada Petani Di Desa Gading, Kabupaten Pasuruan. - Siska, Adela Silviana; K, Alda Sylvia; Archadea, Cawla; Desilva, Melati Putri; Putri, Melinda Aprilia; Rizkiyah, Noor (As-Syirkah: Islamic Economic & Financial Journal, 2024)
The training program on making Liquid Organic Fertilizer (POC) in Gading Village, Pasuruan District, East Java, is a response to two major challenges: the declining allocation of subsidized fertilizers and the infestation of carp snails in rice crops. This initiative aims to turn threats into opportunities by utilizing carp snails and papaya peel waste as raw materials for POC. Through collaboration between PT Lembaga Sahabat Petani and UPN "Veteran" East Java students, the training was conducted using a theoretical and hands-on approach. The methods used included Focus Group Discussion (FGD) and demonstration of POC making. The results of the training show significant potential in improving agricultural productivity and farmers' welfare, although long-term evaluation is still needed. The program offers an economical and environmentally friendly solution to overcome dependence on chemical fertilizers and support sustainable agriculture. Suggestions for development include periodic monitoring, development of distribution networks, involvement of local government, further research, and establishment of farmer groups specifically for POC production and development.